Productivity Growth in Agriculture An International Perspective - Fuglie, Keith O (CABI, 2014)
Improving agricultural productivity has been the world’s primary defence against a Malthusian crisis – the idea that food demand from a rising population will con- front limits to natural resources and lead to famine. In fact, throughout the 20th century real (inflation-adjusted) agricultural prices fell (Giovanni, 2005), implying supply was growing faster than demand, in spite of a global population increase of 3.7 times (United Nations, 2004). Hayami and Ruttan (1971, 1985) showed that the agricultural success story of the 20th century was increasingly about raising the productivity of agricultural resources, rather than expand- ing the resource base. Figure 1.1 updates a graphical depiction of long-term trends in agricultural land and labour productivity that was popularized in the texts of Hayami and Ruttan (1971, 1985). The graph shows the progression in output per worker and output per area for major global regions dur- ing the past 50 years. Generally, industrial- ized nations have defined, and steady pushed out, the ‘technology frontier’, or the highest land- and labour-productivity com- binations. Currently, SE Asia, China and Latin America are approaching the produc- tivity levels that today’s industrialized nations were at in the 1960s.